2020
DOI: 10.3390/app10228163
|View full text |Cite
|
Sign up to set email alerts
|

Macro-Modelling Approach for the In-Plane Cyclic Response of Cold-Formed Steel Partition Walls

Abstract: Past earthquakes demonstrate that non-structural elements could be vulnerable to a relatively low intensity ground shaking which induces negligible structural damage. The study aims to improve previously developed macro-models of cold-formed steel (CFS) partition walls to properly capture their in-plane cyclic response and damage states of important components in a CFS partition wall under imposed excitation. An effective analytical modelling approach is adopted for a simple modelling procedure and less comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Recent studies clarified that the aspect ratio of the partitioning walls highly affects the load-bearing capacity and the energy dissipation of these components. [20] Previous researchers [14,19] developed the detailed finite element models only for discrete aspect ratio levels of the walls. This problem results in having the dynamic properties of the walls with limited aspect ratio levels.…”
Section: Capacity and Energy Bounds For Wallsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies clarified that the aspect ratio of the partitioning walls highly affects the load-bearing capacity and the energy dissipation of these components. [20] Previous researchers [14,19] developed the detailed finite element models only for discrete aspect ratio levels of the walls. This problem results in having the dynamic properties of the walls with limited aspect ratio levels.…”
Section: Capacity and Energy Bounds For Wallsmentioning
confidence: 99%
“…Macillo et al [18] developed a spring-based model to calibrate the seismic behavior of cold-formed steel strap braced stud walls. Shin and Kim [19] presented an analytical modeling procedure for cold-formed steel partition walls in which the cyclic behavior of different components was simulated by lumped spring elements. Salmasi et al [20] proposed a practical approach for the derivation of analytical fragility curves of partition walls.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research on the partition walls discusses the details of the damage patterns observed in quasi-static tests [2][3][4][5][6][7][8][9][10][11] and shaking table tests. [12][13][14][15][16][17][18][19][20] Many reports discussed the damage variations with construction details, 6,7,12,14,20,21 and the damage mainly occurred in the corners, edges, and screw connections of panels.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several past studies have proposed damage mechanism models based on the local damage phenomena of partition walls such as models for the explanation of panel separation from the stud by panel rotation, 17 the failure of welding and panel fixation by out-of-plane rotation, 12 and the connection damages between panels and studs. 11,23 However, a damage mechanism that explicitly accounts for the boundary flexibility has not been presented yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation